2009
DOI: 10.1021/es901685u
|View full text |Cite
|
Sign up to set email alerts
|

An 800-Year Record of Atmospheric As, Mo, Sn, and Sb in Central Asia in High-Altitude Ice Cores from Mt. Qomolangma (Everest), Himalayas

Abstract: As, Mo, Sn, and Sb have been determined by inductively coupled plasma sector field mass spectrometry (ICP-SFMS) in 143 depth intervals of high-altitude ice cores from Mt. Everest, covering an 800-year time period from 1205 to 2002 AD. The results clearly demonstrate the long-term historical record of atmospheric transport and deposition of As, Mo, Sn, and Sb that has prevailed at high altitudes in the central Himalayas. Natural contributions, mainly from mineral dust, have dominated the atmospheric cycles of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 33 publications
(48 reference statements)
3
50
0
1
Order By: Relevance
“…The results illustrated that high altitude atmosphere on the southern Plateau might be more sensitive to variations in the anthropogenic emissions than that in the central Himalayas. Trace element deposition in the snowpacks at the Laohugou (LHG) and the Tanggula (TGL) glacier basins in the northern Plateau was studied by Dong et al (2015), while Kaspari et al (2009) and Hong et al (2009) respectively investigated the concentrations of trace metals in ice core from Mt. Qomolangma.…”
Section: Major and Trace Elements In Environmental Media Of The Qinghmentioning
confidence: 99%
See 1 more Smart Citation
“…The results illustrated that high altitude atmosphere on the southern Plateau might be more sensitive to variations in the anthropogenic emissions than that in the central Himalayas. Trace element deposition in the snowpacks at the Laohugou (LHG) and the Tanggula (TGL) glacier basins in the northern Plateau was studied by Dong et al (2015), while Kaspari et al (2009) and Hong et al (2009) respectively investigated the concentrations of trace metals in ice core from Mt. Qomolangma.…”
Section: Major and Trace Elements In Environmental Media Of The Qinghmentioning
confidence: 99%
“…Kaspari et al (2009) reported that atmospheric trace metal concentrations widely increased with regionally varied enrichment according to comparison of trace metal concentrations in different ice cores. Hong et al (2009) concluded that natural sources (mainly from mineral dust) dominated the atmospheric cycles of As, Mo, Sn during the 700 years prior to the 20th century and anthropogenic emissions of these elements (largely from stationary fossil fuel combustion and nonferrous metals production) contributed to the pronounced increases of both concentrations and crustal enrichment factors since the 1970s. They speculated that the increased concentrations of metals were attributed to anthropogenic emissions mainly including stationary fossil fuel combustion and nonferrous metals production.…”
Section: Major and Trace Elements In Environmental Media Of The Qinghmentioning
confidence: 99%
“…Even in a high altitude atmosphere, the content of Mt. Everest's ice core has shown to have rising arsenic levels since the 1970s, representing a significant amount of arsenic accumulation (Hong et al, 2009). The impacts of arsenic to these media are a cause for serious concern due to their high toxicity, persistency, and the ability of long-range transportation in the environment (Ng et al, 2003, Kang et al, 2011, De Temmerman et al, 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Preindustrial Pb concentration increases in Greenland have been linked to Pb mining and smelting performed in the Mediterranean region during the Greek, Roman, and Medieval periods (8,12), indicating the hemispheric-scale impact of early anthropogenic activities. In contrast, ice cores recovered from midlatitudes provide evidence for anthropogenic aerosol emissions from the late 19th century in the European Alps (13,14) and from the middle of the 20th century in the Himalaya (6,15). This suggests an asynchronous postindustrial impact on the atmosphere in various parts of the Northern Hemisphere.…”
mentioning
confidence: 96%
“…Ice cores from the remote polar ice sheets and high-altitude glaciers receive trace elements exclusively from the atmosphere (4,5) and can therefore be used to precisely assess the possible large-scale impact of anthropogenic activities through time (6,7). In this respect, they also offer a unique, global perspective on current efforts to define the onset of the Anthropocene as defined by the International Union of Geological Sciences.…”
mentioning
confidence: 99%